Gênero, cidadania e educação - Brabo, Tânia Suely Antonelli Marcelino (Editora Oficina Universitária, 2023)
The reflections begin with the content emphasizing the moment we are experiencing, with actions aimed at attacking human rights and their defenders, including advances in terms of legislation and public policies that deal with women's rights, resulting tireless struggle of feminist movements in our country.